2020
DOI: 10.1002/adma.202002812
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Grazing‐Incidence Wide‐Angle Scattering Reveals Mechanisms for Phase Distribution and Disorientation in 2D Halide Perovskite Films

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as doi: 10.1002/smll.adma202002812.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 46 publications
4
104
0
Order By: Relevance
“…Kanatzidis and co‐workers [ 98 ] divided the crystallization process of 2D perovskite into three stages: i) disordered colloidal sol–gel, ii) an oriented 3D‐like phase, and iii) oriented 2D phase. Among them, the first stage can also be called the intermediate stage, it is evident that the film forming process of 2D perovskite is closely related to the precursor.…”
Section: Crystallization Kineticsmentioning
confidence: 99%
“…Kanatzidis and co‐workers [ 98 ] divided the crystallization process of 2D perovskite into three stages: i) disordered colloidal sol–gel, ii) an oriented 3D‐like phase, and iii) oriented 2D phase. Among them, the first stage can also be called the intermediate stage, it is evident that the film forming process of 2D perovskite is closely related to the precursor.…”
Section: Crystallization Kineticsmentioning
confidence: 99%
“…Previous studies have shown that there are three stages in the film formation of 2D perovskite: initial nucleation from the sol–gel at the air/liquid interface giving an oriented 3D‐like phase, secondary nucleation on the grown 3D‐like phase and homogeneous nucleation inside the solution forming a less‐oriented 2D phase, and reorientation/rearrangement of already‐formed crystals. [ 23 ] In fact, dominating nucleation at the air/liquid interface would make the highly oriented 3D‐like perovskite seed the layered perovskites and promote the favorable out‐of‐plane orientation. [ 7 ] Oppositely, multiple nucleation events are a major cause of disorientation, [ 7 ] and the high secondary nucleation density will result in small‐grain 2D phases with substantial boundaries according to classical nucleation and growth models.…”
Section: Figurementioning
confidence: 99%
“…Both NH 4 Cl and NH 4 I x Cl 1−x -contained films express strong, sharp, and discrete Bragg spots, suggesting the directional alignment. [23,24] The absence of diffraction spots along q z between 0 and 1 Å −1 together with the clear characteristic absorption peaks of the layered perovskite (Figure S4, Supporting Information) suggests the dominated out-of-plane orientation. [25,26] The more concentrated and intense diffraction spots for the NH 4 I x Cl 1−x film demonstrate not only better crystallinity but also a higher degree of out-of-plane orientation, possibly attributed to the enhanced crystal quality and alignment.…”
mentioning
confidence: 99%
“…[ 16,19–31 ] The origin of the 2D perovskite layer orientation and the crystallization kinetics were thus intensely studied using grazing‐incidence wide‐angle X‐ray scattering (GIWAXS). [ 32–36 ]…”
Section: Introductionmentioning
confidence: 99%
“…[16,[19][20][21][22][23][24][25][26][27][28][29][30][31] The origin of the 2D perovskite layer orientation and the crystallization kinetics were thus intensely studied using grazing-incidence wide-angle X-ray scattering (GIWAXS). [32][33][34][35][36] The design of perovskite-based PV and LED devices typically features either planar or bulk heterojunctions, making the crystal orientation essential in the former case and the crystal size critical in the latter case. [37] The substrate effect has been studied in great detail, particularly the aspects of charge collection properties, [38,39] induced elemental separation, [40,41] and film morphology.…”
Section: Introductionmentioning
confidence: 99%